Performance of History of Physics Course Through a Local Wisdom: “Wayang” - Saidatul Khoiriyah; FX Krisna Kurniawan; Faradila Aulia' Alifteria; Angki Yustito Dulim; Nadi Suprapto (Studies in Philosophy of Science and Education, 2021)
This article about scientific puppets aims to explain or describe the concept of a scientific puppet, how to make a scientific puppet, as well as the implementation and implications of puppet art as a medium of learning physics. In this case, the scientific puppet can be a learning medium for the knowledge of the history of physics scientists to students and students. The preparation of this article uses the type of descriptive qualitative research because as an interpretation and description of the concept of cultural acculturation used for learning physics, the implementation of scientific puppets as a method of learning physics. In this article produces a discussion of the concept of a scientific puppet, a puppet that presents a scientist with an actual picture of the scientist but is shaped in such a way that it is shaped like a puppet. The wayang scientist procedure starts by designing the drawings of the characters in the story to be displayed. The figures that will be used in the puppets are edited to use clothing that suits the setting of the place and atmosphere. After that, cut and placed on used cardboard so that it can be erect and given wood as a mastermind handle. The implementation of the story used is the story of a physicist J Black and JP Joule. In this case, the teacher acts as a puppeteer. The teacher uses the scientific puppet as a visual aid to present physics material through a pre-packed story. The implications of this puppet are interesting and impressive because the material of physics history is easier to understand.